Overvaluation of shape and weight in adolescents with anorexia nervosa: does shape concern or weight concern matter more for treatment outcome?. Issue 1 (December 2015) - Byrne, Catherine; Kass, Andrea; Accurso, Erin; Fischer, Sarah; O'Brien, Setareh; Goodyear, Alexandria; Lock, James; Le Grange, Daniel
Abstract Background Overvaluation of shape and weight is a key diagnostic feature of anorexia nervosa (AN); however, limited research has evaluated the clinical utility of differentiating between weight versus shape concerns. Understanding differences in these constructs may have important implications for AN treatment given the focus on weight regain. This study examined differences in treatment outcome between individuals whose primary concern was weight versus those whose primary concern was shape in a randomized controlled trial of treatment for adolescent AN. Methods Data were drawn from a two-site randomized controlled trial that compared family-based treatment and adolescent focused therapy for AN. Chi-square tests and logistic regression analyses were conducted. Results Thirty percent of participants presented with primary weight concern (n  = 36; defined as endorsing higher Eating Disorder Examination (EDE) Weight Concern than Shape Concern subscale scores); 60 % presented with primary shape concern (n  = 72; defined as endorsing higher EDE Shape Concern than Weight Concern scores). There were no significant differences between the two groups in remission status at the end of treatment. Treatment did not moderate the effect of group status on achieving remission. Conclusions Results suggest that treatment outcomes are comparable between adolescents who enter treatment for AN with greater weight concerns and those who enter treatment with greater shape concerns. Therefore, treatment need not be adjusted based on primary weight or primary shape concerns.